Kajian Filsafat dan Teologi Perspektif Thomas Aquinas dan Al-Kindi untuk Memperkuat Pendidikan Agama di Indonesia - Muhammad Luthfi Jalaludin Al-Habibi (UIN Sunan Gunung Djati Bandung, 2023)
This study aims to examine the philosophy and theology perspectives of Thomas Aquinas and Al-Kindi to strengthen religious education in Indonesia. This study uses a qualitative approach by applying descriptive methods. The formal object of this research is philosophy and theology in the view of Thomas Aquinas and Al-Kindi. While the material object is religious education in the Indonesian context. The results and discussion in this study show that Thomas Aquinas, a Western figure, and Al-Kindi, an Eastern figure, have the same views in the correlation of philosophy and religion. First, all creation is the result of the most important nature and nothing comes first from Allah SWT. Second, regarding the nature of the main cause is something that has no beginning and no ending, namely Allah SWT. This research concludes that Thomas Aquinas and Al-Kindi's thoughts on philosophy and religion and the correlation between the two can be realized and developed to strengthen education in Indonesia. This research has limitations without conducting field studies, so this is an opportunity for further research for empirical studies, then this research recommends to future researchers to conduct a more in-depth analysis to study religious education in Indonesia.